Identity reinforcement or risky organizational change? Category spanning in humanitarian projects - Eva A. P. Kooijman; Nikolaus Beck (Administrative Sciences, 2021)
In this study, we investigate the consequences of organizational change that consist of adding new categories to the portfolio of humanitarian organizations. Our aim is to discern differences in these consequences between specialist and generalist organizations. Previous research has shown that spanning categories lead to disadvantages in the evaluation of organizations by audience members in terms of the attention they receive from the audience but did not focus on the distinction between specialists, organizations that have no history in spanning categories, and generalists, organizations that have already done so in the past. Using fixed effect logit regression methods on project approval among 2480 non-governmental organizations (NGOs) in the humanitarian sector, we show that category spanning is tantamount to risky organizational change for specialist organizations, which leads to a reduction in project approval. However, generalists benefit from category spanning, which indicates identity reinforcement. We also show that in the case of urgent demand, spanning categories has a less detrimental effect. Consequently, organizations that have successfully undergone a change from a specialist to a generalist identity no longer suffer from category spanning. Moreover, also situations of urgent demand reduce the negative consequences of category spanning.
Keywords: 350; category spanning; humanitarian organizations; non-governmental organizations; organizational change; organizational decision-making; organizational ecology